Fifteen-year Outcomes Following Conservative Management Among Men Aged 65 Years or Older with Localized Prostate Cancer - Lu-Yao, Grace L. (Eur Urol, 2015)
BACKGROUND: To understand the threat posed by localized prostate cancer and the potential impact of surgery or radiation, patients and healthcare providers require information on long-term outcomes following conservative management. OBJECTIVE: To describe 15-yr survival outcomes and cancer therapy utilization among men 65 years and older managed conservatively for newly diagnosed localized prostate cancer. DESIGN, SETTINGS, AND PARTICIPANTS: This is a population-based cohort study with participants living in predefined geographic areas covered by the Surveillance, Epidemiology, and End Results program. The study includes 31 137 Medicare patients aged ≥65 yr diagnosed with localized prostate cancer in 1992–2009 who initially received conservative management (no surgery, radiotherapy, cryotherapy, or androgen deprivation therapy [ADT]). All patients were followed until death or December 31, 2009 (for prostate cancer–specific mortality [PCSM]) and December 31, 2011 (for overall mortality). OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Competing-risk analyses were used to examine PCSM, overall mortality, and utilization of cancer therapies. RESULTS AND LIMITATIONS: The 15-yr risk of PCSM for men aged 65–74 yr diagnosed with screening-detected prostate cancer was 5.7% (95% confidence interval [CI] 3.7–8.0%) for T1c Gleason 5–7 and 22% (95% CI 16–35%) for Gleason 8–10 disease. After 15 yr of follow-up, 24% (95% CI 21–27%) of men aged 65–74 yr with screening-detected Gleason 5– 7 cancer received ADT. The corresponding result for men with Gleason 8–10 cancer was 38% (95% CI 32–44%). The major study limitations are the lack of data for men aged < 65 yr and detailed clinical information associated with secondary cancer therapy. CONCLUSIONS: The 15-yr outcomes following conservative management of newly diagnosed Gleason 5–7 prostate cancer among men aged ≥65 yr are excellent. Men with Gleason 8–10 disease managed conservatively face a significant risk of PCSM. PATIENT SUMMARY: We examined the long-term survival outcomes for a large group of patients diagnosed with localized prostate cancer who did not have surgery, radiotherapy, cryotherapy, or androgen deprivation therapy in the first 6 mo after cancer diagnosis. We found that the 15-yr disease-specific survival is excellent for men diagnosed with Gleason 5– 7 disease. The data support conservative management as a reasonable choice for elderly patients with low-grade localized prostate cancer.